Atypical Presentation of Typhoid Fever - Madi, Deepak; Achappa, Basavaprabhu; Ramapuram, John T; Chowta, Nithyananda; Laxman, Mridula; Mahalingam, Soundarya (Asian Journal of Medical Sciences, 2013)
The classical presentation of typhoid has changed over the years. Atypical presentation of typhoid is now seen in clinical practice. Entericfever can present with atypical manifestations like abdominal lymphadenopathy, acute acalculous cholecystitis, osteomyelitis, splenic abscess and Pneumonia. Jaundice splenic abscess and thrombocytopenia in a febrile patient in the tropics is commonly due to Malaria, Leptospirosis and Dengue. We report a case of typhoid fever presenting with jaundice and thrombocytopenia. A 17 year old male presented to us with history of fever and jaundice. Investigations revealed thrombocytopenia and conjugated hyperbilirubinemia. Blood culture grew Salmonella Typhi. He was treated with ceftriaxone and he improved. A diagnosis of typhoid fever must be considered in a febrile patient with jaundice and thrombocytopenia in the tropics. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8584 Asian Journal of Medical Science, Volume-5(2) 2014: 140-142